2021
DOI: 10.1016/j.parkreldis.2020.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Exome-wide rare variant analysis in familial essential tremor

Abstract: Introduction: Essential tremor (ET) is one of the most common movement disorders. Despite its high prevalence and heritability, its genetic etiology remains elusive with only a few susceptibility genes identified and poorly replicated. Our aim was to find novel candidate genes involved in ET predisposition through whole exome sequencing. Methods: We studied eight multigenerational families (N = 40 individuals) with an autosomal-dominant inheritance using a comprehensive strategy combining whole exome sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Indeed, a recent whole-exome sequencing of eight autosomal-dominant ET families of Spanish origin revealed the absence of rare functional variants co-segregating with ET in more than two families. 23 Specifically, the study identified 15 ET-segregating rare variants with 13 of them family-specific, which indicates significant genetic heterogeneity of ET even within the same ethnic group.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, a recent whole-exome sequencing of eight autosomal-dominant ET families of Spanish origin revealed the absence of rare functional variants co-segregating with ET in more than two families. 23 Specifically, the study identified 15 ET-segregating rare variants with 13 of them family-specific, which indicates significant genetic heterogeneity of ET even within the same ethnic group.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, family history, is not even included in the diagnostic criteria for ET by the Consensus Statement on the Classification of Tremors [50]. Gene variants which segregate with ET in kindred studies may often not be significantly associated with ET in larger case-control analyses [116]. Establishing a genetic link between ET and PD consequently remains challenging despite these reported kindreds.…”
Section: Essential Tremormentioning
confidence: 99%
“…Its hallmark clinical feature is kinetic tremor, although additional motor and non-motor features may occur [2,3]. ET clusters or aggregates within families [4][5][6][7][8] and greater proportions of ET probands have relatives diagnosed with ET than do non-ET probands [9]. In one analysis, first-degree relatives of ET probands were approximately five times more likely to be diagnosed with ET than were first-degree relatives of control probands [10].…”
Section: Introductionmentioning
confidence: 99%